AI Role in Optimizing Smart Library and Co-Working Space Services for Millennials - Novida, Krisna Audy; Putri, Alya Khansa; Agustina, Salfia; Pratiwi, Kurniasih Yuni; Putra, Endry; Putri, Kethy Hariyadi (Brawijaya University Library, 2024)
AI enhances library services in the digital era by improving efficiency, personalization, and data management, while supporting research, education, and global information access despite initial challenges. This research employs a literature study method, collecting and analyzing data from Google Scholar on AI in libraries to address the research questions. This research explores how AI enhances the efficiency, accessibility, and quality of digital library services, addressing challenges in privacy, ethics, and librarians' roles while highlighting the need for a sustainable approach. This research highlights AI's role in enhancing digital library services through improved information retrieval, personalization, and data analysis, while addressing challenges in privacy, data security, and ethics. AI in digital libraries aims to enhance efficiency, service quality, and user experience, highlighting its potential for inclusivity and innovation with recommendations for future research.